2014
DOI: 10.1051/tpe/2014009
|View full text |Cite
|
Sign up to set email alerts
|

« Health Literacy » et éducation thérapeutique du patient : Quels rapports conceptuel et méthodologique?

Abstract: Introduction : Alors que le nombre d'études traitant de la « Health Literacy » (HL) est en pleine augmentation depuis ces dix dernières années, de nombreuses recherches ont mis en évidence l'impact significatif du niveau de HL sur l'état de santé des personnes. Plus récemment, un constat met en évidence qu'un faible niveau de HL constituerait un obstacle potentiel à l'accès à l'éducation thérapeutique du patient (ETP). Il en découle un questionnement quant au rapport entre ces deux champs de pratiques et d'étu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Furthermore, the World Health Organization emphasizes the central role of HL in addressing health inequalities worldwide [1]. Nevertheless, HL has been studied only sparsely in France, likely due to the lack of adequate measurement instruments validated in French [8–10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the World Health Organization emphasizes the central role of HL in addressing health inequalities worldwide [1]. Nevertheless, HL has been studied only sparsely in France, likely due to the lack of adequate measurement instruments validated in French [8–10].…”
Section: Introductionmentioning
confidence: 99%
“…11 The HLQ explores health literacy through nine separate conceptually distinct scales whose psychometric properties have been showed to be robust in several languages. [11][12][13][14][15] In France, while a few research teams are exploring health literacy in diabetes, cancer, rheumatic diseases, and its relations to health inequities, health and care pathways, and health education and prevention, [16][17][18][19][20][21][22][23][24] to date no health literacy instrument has been developed or adapted in France with comparable properties as for the HLQ, to allow assessment in communities and across specific populations with the aim of adaptation of services and structures to the health needs of people struggling with disease management or prevention. The present work reports the French translation of the HLQ, the testing of its psychometric properties, and its usefulness in a population of individuals at risk for cardiovascular diseases attending counselling support and education in three community settings in France.…”
Section: Introductionmentioning
confidence: 99%
“…After an analysis of 74 studies, the authors concluded that the major barrier to access and use online health information for individuals with low literacy levels is strongly related to usability. A low level of health literacy can limit patients' access to therapeutic education [54,55] and consequently lessen their commitment [56]. Paasche-Orlow and Wolf [57] even showed that literacy is directly related to health outcomes.…”
Section: Usability Health Literacy and Prior Health Knowledgementioning
confidence: 99%